Sistemas constructivos plegables, caso de aplicación arquitectura emergente. - Criollo Ríos, Tatiana Cecibel (2014)
We live in a media without planning to address both environmental and man-made disasters. This long-term imminent reality becomes an infrastructure problem, which leads us to seek alternative systems of immediate response to help minimize long-term complications such events occur habitability, as well as urban decay. It is for this reason that the present research in the field of architecture, it focuses on the study of folding construction systems, as an alternative method for the manufacture of emerging shelters. The first part of the study comprises all concepts involving the term pop, and the identification of the different aid organizations. Second, we discuss the nature of the folding systems concerning the emerging architecture; then conceive the design of a module that meets the minimum habitability conditions, using locally available materials and have universal character. Finally, we will compare the features of the model designed based on the emergent architecture and with reference to an existing model in the local market.